War of the weeds - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
In eastern Africa, farmers plant napier grass (Pennisetum purpureum) or Sudan grass (Sorghum vulgare sudanese) as a trap weed in maize. The stem borer, accountable for up to 30% yield losses in maize, prefers these grasses to maize. Two other weeds...